The role of urban form for the Productive City - Marat-Mendes, T.; Lopes, S. S.; Fernandes del Pino, R. (XXXII Conference ISUF, 2025)
The history of human civilization testifies to a plethora of urban form solutions associated to uses of economic productivity, across the passage of time or technological advances. Within those examples there are cases of survivors but also of neglection by society itself, with deep impacts on the productivity and sustainability of the city. This presentation aims to disclose the role of urban form on the guaranteeing of a productive city, from the perspective of sustainability and the problematic of climate change. Therefore, it questions possibilities to access the role of urban form from the perspective of a productive city, which should integrate local food production (urban agriculture) or transformation capacities, while operating through sustainable modes of transportation (low carbon emissions). The main purpose of this presentation is to discuss the preliminary results of a specific task, a literature review, which have been conducted for an ongoing research project – HAT - Hyping Agriculture and Transit (HAT) in 15-minute Cities (15mC). The aim of such literature review is to overview and compare in a comparative manner historical examples of urban form associated to food productivity/transformation and sustainable modes of transportation. Finally, we aim to disclose which are the urban form patterns, uses, and specific relations, that appear to provide such conditions of sustainability and productivity/transformation. Moreover, this paper discusses the results of the adopted methodological approach which was based on a morphological comparative analysis of well-known international examples of urban planning proposals retrieved from the literature review, and which were evaluated from their perspective of food production/transformative capacities and spatial outcomes.